The Role of Islamic Religious Education Teachers in Implementing the Concept of Religious Education with a Multicultural Insight at SMA Negeri 2 Metro - Sulthoon, M. Haafidh Ibnu; Aziz, Ikhwan; Hayati, Rina Mida (International Journal on Advanced Science, Education, and Religion, 2025)
The government has the responsibility to prevent conflicts from arising due to cultural differences and social habits. Therefore, the educational policies developed need to reflect this spirit Bhinneka Tunggal Ika, namely unity in diversity. As a form of effort to increase inclusivity in formal education, the government is building schools that are open to all students, regardless of religion, tribe or ethnicity. However, challenges remain. One of them is the delivery of religious lessons in schools which sometimes tends to instill an exclusive understanding that one's own beliefs are the only truth, while the teachings of other religions are considered wrong. This risks giving rise to prejudice, emotional distance, and even hatred between followers of different religions. At SMA Negeri 2 Metro, Islamic Religious Education teachers play an important role in two main aspects of the educational process. First, they convey Islamic teaching material proportionally and contextually in the classroom. Second, they instill universal religious values such as mutual respect, cooperation and tolerance for differences in students' daily lives. Schools also provide space for students to develop as individuals who are able to adapt to social diversity. Through this process, students are taught to accept differences, build trust between others, foster mutual understanding, and be open and trusting in establishing social relationships. In this way, multicultural education is not just a discourse, but a real practice that is able to prevent conflict and violence in social life.